Germany - Burk, V.; Ehnhold, P.; Petry, K.; Steinbach, D. (Comparative elite sport development. Systems, structures and public policy, 2025)
The German sport system can only be understood against the background of its historical development since 1945. Indeed, major historical events continue to impact the structures and development of elite sport in Germany. Against this background, the basic convictions that have emerged from historical experience - and are now deeply anchored in the collective social mindset - determine the general framework and limit the leeway for action within the system.